PERBANYAKAN TUNAS ADVENTIF PORANG DENGAN MENGGUNAKAN BAP DAN TDZ - Lisa Erfa; Rahmadyah Hamiranti; Nanang Wahyu Prajaka; Desi Maulida (Jurnal Penelitian Pertanian Terapan, 2025)
The limited availability of conventional porang seedlings through seeds and tubers is a constraint in the development of this plant because it is time-consuming, seasonal-dependent, and produces non-uniform seedlings. Therefore, an alternative method in the form of tissue culture, known as micropropagation, is needed to produce quality porang seedlings. Micropropagation is a more efficient and profitable plant propagation method than conventional methods because it can produce seedlings in a relatively short time, is not seasonal-dependent, uniform, and free from pathogens. This study aims to determine the response of porang shoot multiplication to various types and concentrations of cytokinin growth regulators. The experiment was conducted using randomized block design. The treatments tested were P1 : BAP 0 mg.l-1 + TDZ 1 mg.l-1 ; P2 : BAP 0 mg.l-1 + TDZ 2 mg.l-1 ; P3 : BAP 0 mg.l-1 + TDZ 3 mg.l-1 ; P4 : BAP 1 mg.l-1 + TDZ 0 mg.l-1 ; P5 : BAP 1 mg.l-1 + TDZ 0,5 mg.l-1 ; P6 : BAP 1 mg.l-1 + TDZ 1 mg.l-1 ; P7 : BAP 2 mg.l-1 + TDZ 0 mg.l-1 ; P8 : BAP 2 mg.l-1 + TDZ 0,5 mg.l-1 ; P9 : BAP 2 mg.l-1 + TDZ 1 mg.l-1 ; P10 : BAP 3 mg.l-1 + TDZ 0 mg.l-1 ; P11 : BAP 3 mg.l-1 + TDZ 0,5 mg.l-1 ; dan P12 : BAP 3 mg.l-1 + TDZ 1 mg.l-1. Each treatment was replicated five times, with five bottles planted in each replication. Data were analyzed using Analysis of Variance, and differences between treatments were assessed using the LSD test at the 5% level. The observed variables were the rate at which explants formed buds, the number of buds, and the multiplication rate. Addition of cytokinin affected the multiplication response of porang buds in vitro. The P6 treatment produced the fastest bud formation rate, the highest number of buds and the highest multiplication rate.